2017
DOI: 10.1159/000457899
|View full text |Cite
|
Sign up to set email alerts
|

Hypodysfibrinogenemia with a Heterozygous Mutation of γCys326Ser by the Novel Transversion of TGT to TCT in a Patient with Pulmonary Thromboembolism and Right Ventricular Thrombus

Abstract: We encountered a 45-year-old Japanese man who suffered from pulmonary thromboembolism and huge right ventricular thrombus after inferior vena cava (IVC) filter implantation without apparent thrombus in either the deep veins or inside the IVC filter. The biochemical data showed a discrepancy in the level of fibrinogen between the immunological and thrombin time methods, suggesting hypodysfibrinogenemia. The sequencing of the fibrinogen γ-chain gene (FGG) revealed a novel heterozygous missense mutation in exon 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Patients with hypodysfibrinogenemia are more prone to develop adverse outcomes than patients with dysfibrinogenemia [36,37]. The bleeding phenotype is usually severe, although dependent on the antigenic fibrinogen levels [38].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with hypodysfibrinogenemia are more prone to develop adverse outcomes than patients with dysfibrinogenemia [36,37]. The bleeding phenotype is usually severe, although dependent on the antigenic fibrinogen levels [38].…”
Section: Discussionmentioning
confidence: 99%
“…These data indicated that substitutions of γp.C352 led to a drastic change in the tertiary structure of the γ-module caused by the destruction of an intra-peptide disulfide bridge, resulting in reduced secretion of variant fibrinogen and impaired function of polymerization. Finally, five out of seven families possessing substitutions of γp.C352, namely, Cordoba [24], Tokai [25],…”
Section: Discussionmentioning
confidence: 99%